Value Co-Creation Strategy Formulation for Tusuk Coffee to Enhance Customer Experience and Satisfaction - Muhammad Rizky Ridhani; Sonny Rustuadi (Jurnal Indonesia Sosial Teknologi, 2024)
The research intends to identify Tusuk Coffee's issues, investigate the possible benefits of value co-creation as a strategic response, and make practical recommendations based on the findings. The study takes a mixed-methods strategy that combines exploratory and confirmatory research techniques. The data from this study were collected using two types of data: primary and secondary data. The primary data was collected using qualitative methods to be conducted with semi-structured interviews with 22 respondents through one-on-one interviews. Data analysis is carried out using qualitative data obtained from in-depth interviews as part of an exploratory phase to gather responses from customers. Subsequently, confirmatory analysis is conducted involving internal stakeholders, suppliers, and experts. The analysis employs thematic analysis, a method well-suited for various research designs. Using the 4P Marketing Mix model and the Value Co-Creation Canvas, the study assesses Tusuk Coffee's present strategies and suggests a customer-centric approach to value creation. The 4P Marketing Mix model was used to examine product, price, place, and promotion strategies. Value co-creation canvas creates a strategy that develops and delivers value by engaging deeply with its customers focusing on nine key areas: value proposition, company capabilities, company resources, the customer's job to be done, the customer's journey, the customer's resources, the customer's desired outcomes, the company's "total customer engagement" value, and the customer's experience value (in-use). This strategy's key elements include providing unique coffee experiences, leveraging digital platforms for community participation, and fostering individualized services to increase consumer loyalty.